(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Various problems institutions of national and state life of the Indonesian people are increasingly approaching concerns. The emergence of movements from the grass roots that undermine the people of this nation are increasingly visible and show an exemplary crisis in the community, so that a series of socio-cultural conflicts occur in the middle of various communities. Socio-cultural conflicts that exist in the life of this nation include separatism, brawls between students / students, terrorism, and other radical movements that are latent. These events reflect the attitude of our violent and anarchist society. The exemplary crisis in society needs to find a solution to the solution so that this nation still exists and is able to compete with other nations. The method used in this partnership program is CIPP based on Context, Inputs, Process and product. CIPP is a social system approach to evaluation. A social system is a set of activities that are interrelated and function together to achieve the mission and goals set in a particular context. In this case, the evaluation is appropriate to improve and assist the achievement of objectives and improvement of the ongoing program, activities within a period of about 8 months. The target audience in this community partnership program is Non-Productive Communities, namely Universities in the City of Surakarta. The target audience was made as a Pancasila Pioneer Universities that needed education and training empowerment in the form of Character Building Training activities as one of the activities that would sustain and filter out socio-cultural conflict problems that arose in the community so that peace and comfort would be achieved in people’s lives. The results of the activities show that character arises when the example has been adapted in the lives of our people. Character needs to be developed and proclaimed, in relation to the depletion of morality. So to overcome the problems of this nation, one of which is to strengthen the United Indonesia Movement in the Context of Implementing the Mental Revolution. While the impact can improve and provide services, and community empowerment.